Nano Online 2016
DOI: 10.1515/nano.11671_2015.201
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity evaluation of cordycepin and its delivery system for sustained in vitro anti-lung cancer activity

Abstract: Cite as: Pornanong Aramwit, Supatra Porasuphatana, Teerapol Srichana, Titpawan Nakpheng. Toxicity evaluation of cordycepin and its delivery system for sustained in vitro anti-lung cancer activity, nano Online (2016). DOI: https://doi.org/10.1515/nano.11671_2015.201Originally published in: Pornanong Aramwit, Supatra Porasuphatana, Teerapol Srichana, Titpawan Nakpheng. Toxicity evaluation of cordycepin and its delivery system for sustained in vitro anti-lung cancer activity, Nanoscale Research Letters. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…also verified that aberrant expression of vimentin and EMT markers E‐cadherin was correlated with the progression of various human cancers. Besides, cordycepin can be incorporated in gelatin type A (GA) for sustaining its release and activity, and higher amount of cordycepin released from GA nanoparticles is shown to have higher antiproliferative and antimigratory effects on A549 lung cancer cells . In the current study, aberrant expression of E‐cadherin, vimentin and MMP‐9 had been observed in both A549 cells and NCI‐H460 cells after being treated with cordycepin.…”
Section: Discussionmentioning
confidence: 99%
“…also verified that aberrant expression of vimentin and EMT markers E‐cadherin was correlated with the progression of various human cancers. Besides, cordycepin can be incorporated in gelatin type A (GA) for sustaining its release and activity, and higher amount of cordycepin released from GA nanoparticles is shown to have higher antiproliferative and antimigratory effects on A549 lung cancer cells . In the current study, aberrant expression of E‐cadherin, vimentin and MMP‐9 had been observed in both A549 cells and NCI‐H460 cells after being treated with cordycepin.…”
Section: Discussionmentioning
confidence: 99%